A vendor-managed inventory system considering the redundancy allocation problem and carbon emissions. Issue 4 (2nd October 2017) - Karimi, Marziyeh; Niknamfar, Amir Hossein
Abstract: This paper presents a novel and practical multi-product Vendor-Managed Inventory (VMI) system reliability in a green supply chain including a single manufacturer and multiple retailers operating in distinct markets without any conflicts of interest. The manufacturer produces several products and dispatches them to the retailers at different wholesale prices under a common replenishment cycle policy. In contrast, the retailers sell the purchased products to customers at different retail prices. On the other hand, the manufacture encounters a Redundancy Allocation Problem (RAP), which is a useful method of enhancing system production reliability. Furthermore, to emphasize global warming and human health concerns as well as to create a green supply chain, this paper considers the tax cost of industrial carbon emissions of all products produced and a limitation on total carbon emissions. Meanwhile, the manufacturer desires to maximize the total production system reliability by adding machines to the production system regarding constraints such as available budget, space and the total tax cost. Therefore, the manufacturer desires to maximize the total net profit as well as the mean time to failure of its production system using a redundancy allocation problem. With this aim, the max–min approach by utilizing GAMS/BARON software is utilized to maximize the minimum ( the worst ) value of the objective functions. Finally, numerical experiments are presented to demonstrate the applicability of the proposed methodology. Sensitivity analysis on the green approach is conducted to provide more insights as well.